2017
DOI: 10.1093/sleepj/zsx050.025
|View full text |Cite
|
Sign up to set email alerts
|

0026 Genetic Loci in Periodic Hypersomnia/Kleine-Levin Syndrome Type

Abstract: Conclusion:In this largest admixture mapping study of AHI in Hispanic/Latino Americans, a novel genomic region was identified to harbor OSA related variants. Future association analysis may identify genetic variants that explain sleep apnea susceptibility and its variation across ancestral groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…KLS is also reported to be associated with HLA‐DQB1*02 (Dauvilliers et al, ), but this association was difficult to replicate (Arnulf et al, ; Lavault et al, ; Nguyen et al, ). A recent genome‐wide association study found a variant in TRANK1 associated with KLS (Hillary et al, ). So far no mutation is identified in KLS and comprehensive genetic analysis of affected individuals is lacking (Raizen & Wu, ).…”
Section: Introductionmentioning
confidence: 99%
“…KLS is also reported to be associated with HLA‐DQB1*02 (Dauvilliers et al, ), but this association was difficult to replicate (Arnulf et al, ; Lavault et al, ; Nguyen et al, ). A recent genome‐wide association study found a variant in TRANK1 associated with KLS (Hillary et al, ). So far no mutation is identified in KLS and comprehensive genetic analysis of affected individuals is lacking (Raizen & Wu, ).…”
Section: Introductionmentioning
confidence: 99%